J.R.R. Tolkien's non-classical myth practices: mytho-logical analysis - Oleksin, Danylo (Ukrainian Cultural Studies, 2024)
Background. The relevance of our research is indicated by the high level of involvement of John Ronald Reuel Tolkien's creative compendium in shaping and constructing modern culture. Over the past twenty-three years of the 21st century, a significant number of projects have articulated and realized their own interpretations of J. Tolkien's mythology. It is enough to mention Peter Jackson's film trilogies, "The Lord of the Rings" (2001-2003) and "The Hobbit" (2012-2014), a series of video games in various genres by Chris Cornell, William Gordon, and Jill Eckhart, such as "The Lord of The Rings: The Battle for Middle-earth" (2004, 2006), Eric Gewirtz's "The Lord of the Rings: Conquest" (2009), John Fleming, Lucas Riting, and Ruf Tomandi's "The Lord of the Rings: War in the North" (2011), among others. Method. Our research's method is based on the mytho-logic method, which involves interpreting myth in the context of its logic and structure (in the interpretation of "The Lord of the Rings" and "The Silmarillion"). Results. An interpretation of "The Lord of the Rings" and "The Silmarillion" in harmony with the logic of myth through its axioms and laws has been carried out, demonstrating the mythic nature of these texts through their full compliance with the axioms and laws of myth logic. The interpretation of "The Lord of the Rings" through structural analysis of selected narrative variants has been articulated. Twelve main mythemes have been identified and their significance for the mythic narrative has been argued. The images of Gollum, Sméagol, Faramir, and Frodo have been interpreted through a mythic matrix, where the first represents the unconscious Shadow of any subject, the second is a subject attempting to contend with it, the third is a subject that conquers it, and the fourth is a sum of the Hero's image, one who has no "simple life" in a "simple world." Conclusions. We consider our mytho-logic to be a valid method for interpreting myths of any spatial and temporal category. It is worth noting that mytho-logic, like any non-classical humanities method, is not purely ideal and does not have all the answers. Any interpretation is an interpretation, neither worse nor better, but the question here lies in the substantiation of conclusions. We deem our research to be substantiated, although unfinished, as new mythemes of "The Lord of the Rings" can and should be explored, new combinations of these mythemes interpreted differently, and explanations offered. This demonstrates the inexhaustibility of meanings in myth, non-classical approaches, and mytho-logic as a method.
Keywords: myth; myth science; myth logic; myth structure; mytho-logic; structuralism; J.R.R. Tolkien; contemporary art